Existence and Multiplicity of Solutions to a Boundary Value Problem for Impulsive Differential Equations - Chunyan He; Yongzhi Liao; Yongkun Li (Journal of Applied Mathematics)
We investigate the existence and multiplicity of solutions to a boundary value problem for impulsive differential equations. By using critical point theory, some criteria are obtained to guarantee that the impulsive problem has at least one solution, at least two solutions, and infinitely many solutions. Some examples are given to illustrate the effectiveness of our results.